2020
DOI: 10.3390/agronomy10040458
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Selected Biochemical and Physical Characteristics and Yielding of Fruits in Apple Cultivars (Malus domestica Borkh.)

Abstract: The aim of the research was to determine selected biochemical and physical characteristics and yielding of fruits in apple varieties (Malus domestica Borkh) such as Gala Schniga, Beni Shogun (Fuji) and Ligol, M.9 rootstock growing in the Wielkopolska region, Poland. high-performance liquid chromatography (HPLC) analysis revealed differences both in the profile and contents of soluble sugars and other metabolites detected in fruits of the tested apple varieties. The highest total saccharide content was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Taste is the main characteristic of fruit quality and has a great impact on the consumer acceptance and purchase decision [ 23 , 24 ]. Sweet and sour are the most important tastes in apple fruits, which are determined by the composition and content of soluble sugars and organic acids [ 25 ]. In this study, four types of sugars including fructose, sucrose, glucose, and sorbitol in ‘Orin’ apples were measured by HPLC ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taste is the main characteristic of fruit quality and has a great impact on the consumer acceptance and purchase decision [ 23 , 24 ]. Sweet and sour are the most important tastes in apple fruits, which are determined by the composition and content of soluble sugars and organic acids [ 25 ]. In this study, four types of sugars including fructose, sucrose, glucose, and sorbitol in ‘Orin’ apples were measured by HPLC ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical compounds of apples determine the quality in terms of not only health but also the economy. Biochemical parameters of apples may be influenced by species, varieties, cultivation conditions, and cultivation techniques [11][12][13][14][15]. Most of the antioxidant activities in apples were fulfilled by polyphenolic antioxidants [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the present research, the highest total phenolics were detected in Granny Smith cultivar. It has been reported that the total phenolics in apples are affected by climate and soil characteristics, the maturity of the fruit, and cultural and technical applications (McGhie et al, 2005;Vieira et al, 2011;Yoon et al, 2020).…”
Section: Resultsmentioning
confidence: 99%